2000
DOI: 10.1021/bp000046w
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Mass Transfer Kinetics in an Enantiomeric Separation System Using a Polymeric Imprinted Stationary Phase

Abstract: Chromatographic data pertaining to the enantioseparation of L- and D-phenylalanine anilide (PA) on a polymeric stationary phase imprinted with L-PA were studied from the viewpoints of phase equilibrium, mass transfer kinetics, and the thermodynamic properties of this enantiomeric separation system. The concentration dependence of the lumped mass transfer rate coefficient (k(m,L)) previously published was analyzed to obtain new information concerning the mass transfer characteristics in this chiral separation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Similar or even higher figures were reported for columns packed with MCTA or silica coated with chemically modified cellulose [7][8][9]. However this is unusual for other types of CSPs [51,52] including brush-type adsorbents [14], in which case the axial dispersion contribution was close to the theoretical limit of 2d p . A similar value of an apparent axial dispersion term for the ChiroSil RCA column was derived from the peak width at half-height.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Similar or even higher figures were reported for columns packed with MCTA or silica coated with chemically modified cellulose [7][8][9]. However this is unusual for other types of CSPs [51,52] including brush-type adsorbents [14], in which case the axial dispersion contribution was close to the theoretical limit of 2d p . A similar value of an apparent axial dispersion term for the ChiroSil RCA column was derived from the peak width at half-height.…”
Section: Resultssupporting
confidence: 82%
“…On the contrary, Da Silva et al [51] reported a fast adsorption for the bupivacain enantiomers on Kromasil CHI-TBB CSP, Asnin et al [14] observed a minor influence of adsorption kinetics comparing to the intraparticle diffusion resistance to the mass transfer for naproxen on Whelk-O1. Miyabe and Guiochon [52] came to the same conclusion studying the adsorption dynamics of phenylalanine on a MIP CSP. As an example of opposite, microcrystalline cellulose triacetate (MCTA) microbeads are to be given.…”
Section: 222mentioning
confidence: 75%
“…Columns packed with them exhibit low efficiency and afford unsymmetrical peaks. One of the origins of the poor properties of imprinted materials is slow mass transfer kinetics inside their particles [32]. In order to evaluate the binding kinetics, adsorption experiments were carried out with PB (pH 7.0, 0.1 mg mL À1 protein) for different times (30,40, 50, 60, 120, 180, 240 min).…”
Section: Binding Kineticsmentioning
confidence: 99%
“…supposed to include spatial recognition between the protein and the imprinted cavities and several binding contributions that derives from the interaction of several aminoacid lateral chains (i.e., hydroxyl of serine, threonine and tyrosine) with boronate groups [18]. Plus, hydrophobic interactions occur between the aromatic structure of the polymer and both the aromatic side chains and the backbone of the protein [32]. For the specific binding, however, three-dimensional effect of recognition sites should play a crucial role when charge environment and adsorbed protein are the same.…”
Section: Samplesmentioning
confidence: 99%
“…However, they also have major drawbacks as packing material for chromatography, such as the extremely tailed peaks and low efficiency. These poor properties originate from heterogeneous energy distribution of the adsorption sites on the surface of the stationary phases and slow mass transfer kinetics inside their particles [4,5]. In addition, they also result in the relatively long time spent in the separation, in particular for the enantioseparation.…”
Section: Introductionmentioning
confidence: 99%